Dietary factors and oral cancer risk: a comprehensive Mendelian randomization analysis in a European population - Shiyang Zhao; Xichen Liu; Qingsen Wang; Shudong Xiao; Wanting Wang; Xinyue Dong; Yourong Jiang; Wen Wu (Discover Oncology)
Abstract Background Oral cancer is one of the most prevalent malignant tumors in the field of oral and maxillofacial surgery. The main etiological factors are tobacco and alcohol, and diet is now considered an important factor in its development. However, it remains to be elucidated whether the associations between specific diets and oral cancer risk are causal. Therefore, in this study, we performed two-sample Mendelian randomization (MR) analyses to estimate the associations of specific diets with the risk of oral cavity cancer (OCC). Methods We conducted a two-sample MR analysis to assess the causal effect of diet on the risk of OCC. Six types of diets, including champagne or white wine (sample size: 175,549), red wine (sample size: 211,628), dried fruit (sample size: 409,125), fresh fruit (sample size: 433,186), average weekly beer plus cider (sample size: 327,634), and never eat eggs, dairy, wheat, sugar: wheat products (sample size: 461,046), were included as exposures. Summary statistics of OCC were obtained from a genome-wide association study (GWAS) including 1223 OCC cases and 2928 controls of European ancestry. We used the inverse-variance weighted (IVW) method as the primary method, with the weighted median and MR Egger used as supplementary methods for causal inference. Sensitivity analyses, including the Cochran Q test, Egger intercept test, MR-PRESSO test, and leave-one-out analysis, were performed to verify the robustness of the MR results. Results The univariate MR showed that champagne or white wine consumption (β = 11.80, p = 0.006), average weekly beer plus cider intake (β = 4.73, p = 0.003), red wine consumption (β = 8.22, p = 0.024), and the never eat eggs, dairy, wheat, sugar: wheat products (β = 14.34, p = 0.002) increased the risk of OCC; Whereas fresh fruit consumption (β = − 3.20, p = 0.038), dried fruit consumption (β = − 2.98, p = 0.012) were protective. The multivariable MR estimates, after controlling for other diets, were as follows: when controlling for the never eat eggs, dairy, wheat, sugar: wheat products and fresh fruit consumption, the effect of average weekly beer plus cider intake on OCC risk was significant, and when controlling for dried fruit consumption, the effect had a P-value close to significant (p = 0.052). The two-step MR showed human characterization: When assessing the impact of dried fruit consumption and fresh fruit consumption, we observed a mediation effect of appendicular lean mass. Furthermore, when assessing the impact of dried fruit consumption and average weekly beer plus cider intake, we observed a mediation effect of standing height. Human system: When exploring the influence of never eat eggs, dairy, wheat, sugar: wheat products, we found a mediation effect of the occurrence of hypothyroidism. Likewise, when assessing the impact of fresh fruit consumption, we found the mediation effect of other diseases of the digestive system. Human metabolite: For the never eat eggs, dairy, wheat, sugar: wheat products, we observed a mediation effect of triglyceride levels in LDL and triglyceride levels in small LDL. Conclusions This study provides champagne or white wine consumption, average weekly beer plus cider intake, red wine consumption, and the never eat eggs, dairy, wheat, sugar: wheat products may increased the risk of OCC; Whereas fresh fruit and dried fruit consumption may were protective. This study analyzed the pathways by which dietary factors influence OCC in aspect of human characterization, human system, and human metabolite. These findings may help inform future research on preventing or treating OCC by modifying dietary factors.